A study on the objective of Malaysian competition law / Izwar Abdul Aziz, Dzulqarnain Ab Fatar and Mohd Kamarul Anwar Mohd Suhaimi. - Abdul Aziz, Izwar; Ab Fatar, Dzulqarnain; Mohd Suhaimi, Mohd Kamarul Anwar (Faculty of Law, 2012)
This project in its present form is the result of a study conducted on the objectives of competition law. The purpose for this project was to review the compatibility of the objective of the Malaysian Competition Act 2010 with the objective of other relevant economic policies such as the Economic Transformation Programme and the country's trade policy. The objective of the Malaysian Competition Act 2010 was reviewed by means of a qualitative research and library research. Competition objectives can be of the consumer welfare approach or of the total economic approach. The Malaysian Competition law however adopted the approach of consumer welfare as its goal. Thus this study also reviewed on the relationship of the Competition Act 2010 with other economic policies, and attempt to point out the effect of inconsistencies towards the consumers and the application of the law. The contributions of this project paper are among other to suggest the suitable approach to be adopted by Malaysian competition law. The next is to propose certain improvement to the application of that law.